T cell-derived small extracellular vesicles in cancer–immune interactions - Ma Janelle Chichoco Garcia; Su Su Thae Hnit; Elena Shklovskaya; Yuling Wang (Cancer Immunology, Immunotherapy, 2025)
Abstract Small extracellular vesicles (sEVs) are lipid-encapsulated nanoparticles released following the endocytic fusion of multivesicular bodies with the plasma membrane. sEVs are secreted by most eukaryotic cells, and they contain proteins, RNAs and DNA. They act primarily as mediators of intercellular communication through the transport of their contents from donor to recipient cells. Immune cells, including T cells, secrete sEVs following activation. T cell-derived sEVs (T-sEVs) have gained attention in cell-to-cell signalling and as promising immunotherapeutic agents. Growing evidence suggests that T-sEVs are key players in cancer immunotherapy responses. A better understanding of T-sEVs production and properties is key for grasping their biological functions. Extensive current literature on tumour-derived sEVs and their applications in diagnostics or therapeutics is in disconnect with fewer reports on T-sEVs. In this review, we discuss T-sEV biogenesis, their roles in cell-to-cell communication and potential applications in immunotherapy for cancer.